Surgical treatment of osteonecrosis associated with bisphosphonates: a case report - Barin, Luisa Machado; Pillusky, Fernanda Maia; Barcelos, Raquel Cristine Silva; Escobar, Carlos Alberto Bazaglia; Danesi, Cristiane Cademartori (Brazilian Dental Science, 2017)
Bisphosphonates (BP) are routinely used in the management of metastatic bone diseases and malignancies neoplasms, but there is an adverse effect of their chronic use called bisphosphonate-related osteonecrosis of the jaw (BRONJ). Treatment for BRONJ is challenging and complex, as there is still no definitive treatment protocols and the various treatments described in the literature have success variables indexes. In this sense, this study aims to emphasize the responsibility of dentist about the knowledge of BRONJ and report a clinical case that the surgical therapy was the best treatment option. Male patient, sixty-nine years old, asked for dental care complaining about bone exposure. On the anamneses, he reported the use of BP due to cancer history. The intra oral examination revealed exposed bone in the lower right molar region extending to retromolar trigon region on lingual side. There was conservative treatment with antibiotic therapy and mouth rinses of chlorhexidine 0.12 %, but not obtaining success. Therefore, we opted for the surgical removal of necrotic bone area and the tooth involved. The postoperative was within normal standard. The knowledge of dentist about this pathology is essential to prevent, diagnose and treat this disease the most appropriate way. Although the treatment of BRONJ remains challenging and complex, surgical therapy is a treatment option for lesions in early clinical stages and resistant to conservative treatment, providing a better prognosis and quality of life for the patient. KeywordsBisphosphonate-associated osteonecrosis; Mandible; Oral surgical procedures.